Digital Innovation and Sustainability: Transforming the Tourism and Hospitality Industry - Kumari, Madhu; Rani, Pooja; Gopal, Chander (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2026)
Digital technology has significantly impacted the tourism and hospitality industry, requiring companies to adapt to changing customer expectations. Advanced technology like AI, mobile apps, IoT, and VR/AR have empowered cutting edge tourists seeking personalized, seamless, and immersive journey reviews that create unforgettable tales. The industry has moved far from conventional, uniform offerings, thanks to those upgrades, towards client-driven styles, enabling organizations to cater to man or woman picks in real-time. AI tools such as predictive analytics and chatbots improve customer by providing tailored hints and immediate assistance. A while has streamlined booking, pricing, and communication strategies, supplying a reachable and on-the-move experience for vacationers. IoT-enabled smart devices include room automation and voice control systems, catering to tech-savvy travelers; virtual and augmented reality technology allows customers to explore destinations and accommodations virtually, influence travel decisions, and increase satisfaction. This study explores how these digital technologies are shaping customer expectations and how the tourism and hospitality industry must adapt to remain competitive. It emphasizes the need for businesses to integrate these technologies into their service models to meet the increasing demand for convenience, privacy, and sustainability by examining these trends. This study provides valuable insights for businesses hoping to renew, customer loyalty in an increasingly digital marketplace. The study employs a systematic literature review methods to examine the impact of these technologies on the behavior and decisions of patrons. The increasing use of AI for predictive analytics is highlighted in industry papers and case studies instantaneous communication and customized recommendations. The results also explore the role of cellular-first techniques in further detail. This is done through features such as bookings app and virtual wallets. In addition to catering to tech-savvy travelers, this is to ensure easy interaction. The studies also examine how smart technology can enhance guest pleasure through computerized processes and room personalization.
Keywords: Digital Technologies; Customer Expectations; Tourism and Hospitality Industry; Artificial Intelligence; Sustainability; Innovation